2018
DOI: 10.1638/2017-0140.1
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF A SMARTPHONE-BASED ELECTROCARDIOGRAM DEVICE WITH A STANDARD SIX-LEAD ELECTROCARDIOGRAM IN THE ATLANTIC BOTTLENOSE DOLPHIN (TURSIOPS TRUNCATUS)

Abstract: A bipolar, single-lead electrocardiogram (ECG) device is capable of recording ECGs with an integrated smartphone application. To determine the utility of this device, phone-based ECGs (pECG) were compared with standard six-lead ECGs (sECG) in four female Atlantic bottlenose dolphins ( Tursiops truncatus) at the National Aquarium. Study animals were trained to haul out onto a dry deck in ventral recumbency and allow simultaneous 30-sec ECG acquisition using the two devices. The pECG device was held against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…One alternative proxy could be to use the changes in f H associated with each breath, the Respiratory Sinus Arrhythmia (RSA) (de Burgh Daly, 1986). While RSA is universally present in a number of air-breathing vertebrates such as the toad, horse, dog, seal, and dolphin (Scholander, 1940; Hayano et al, 1996; Cooper et al, 2003; Noren et al, 2004; Harms et al, 2013; Zena et al, 2017; McDonald et al, 2018; Yaw et al, 2018; Piccione et al, 2019), and even in air-breathing fish (Grossman and Taylor, 2007), its physiological significance is debated (Hayano et al, 1996; Yasuma and Hayano, 2004). It has been suggested that RSA improves gas exchange by enhancing the ventilation-perfusion matching and reduces cardiac work (Yasuma and Hayano, 2004; Ben-Tal et al, 2012, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One alternative proxy could be to use the changes in f H associated with each breath, the Respiratory Sinus Arrhythmia (RSA) (de Burgh Daly, 1986). While RSA is universally present in a number of air-breathing vertebrates such as the toad, horse, dog, seal, and dolphin (Scholander, 1940; Hayano et al, 1996; Cooper et al, 2003; Noren et al, 2004; Harms et al, 2013; Zena et al, 2017; McDonald et al, 2018; Yaw et al, 2018; Piccione et al, 2019), and even in air-breathing fish (Grossman and Taylor, 2007), its physiological significance is debated (Hayano et al, 1996; Yasuma and Hayano, 2004). It has been suggested that RSA improves gas exchange by enhancing the ventilation-perfusion matching and reduces cardiac work (Yasuma and Hayano, 2004; Ben-Tal et al, 2012, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In horses, similar isolated arrhythmias are seen commonly due to high vagal tone and are not necessarily indicative of cardiac pathology, especially if they are infrequent, isolated, and disappear with exercise [43,[71][72][73][74][75]. In dolphins, isolated premature complexes have been reported in dolphins at rest [25], as well as during dives, and are thought to be related to the interplay of sympathetic and parasympathetic tone [26], as in horses. In the authors' experience, isolated premature complexes or isolated instances of atrioventricular block are seen fairly commonly in managed dolphins both in and out of water, and are of little clinical significance, though true prevalence studies have yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…There were no baseline cardiac data on the BB dolphin population prior to the DWH spill, and there is a paucity of information about dolphin cardiac health in general. Recent studies have laid the foundation for cardiac assessment techniques in cetaceans, including electrocardiography (ECG) in managed and free-ranging cetaceans [24][25][26][27][28][29] and echocardiography in dolphins managed under human care [30][31][32][33]. In this study, techniques for advanced cardiac assessment were refined with managed care dolphins, then applied to free-ranging dolphins in BB and dolphins outside of the oil spill footprint in SB.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, initial steps have been taken to develop antemortem diagnostic cardiac tools in an effort to better understand dolphin cardiology. ECG techniques were first described in dolphins in 1970 (40), and comprehensive findings in putatively healthy dolphins were described by Harms et al (41), with additional reports in managed and free-ranging dolphins and other cetaceans in the last two decades (42)(43)(44)(45)(46). Continued research and investigation have laid the foundation for echocardiographic assessment in managed dolphin populations.…”
Section: Introductionmentioning
confidence: 99%